2019
DOI: 10.21203/rs.2.13284/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of fully immunization among children aged 12-23 months in Ethiopia. Further analysis of the 2016 Ethiopian Demographics Health Survey

Abstract: Back ground: Immunization has become the most effective public health measure for the control vaccine preventable disease. It can avert 2 to 3 million children deaths annually. Eighty eight percent of under one year children received diphtheria-tetanus-pertussis in 2015, however still an estimated 19.4 million infants worldwide missed out on basic vaccines. This analysis aims to identify determinant factors for fully immunization among children aged 12-23 months in Ethiopia. Methods: The analysis done based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…The study discovered that children's immunization status was greatly influenced by their region. This finding is in line with research from Ethiopia [11,17,27], which found that non-immunization was higher in the Afar, Oromia, and Somali regions. Compared to children in urban areas, children from rural areas were more likely to be in the worst category of immunization status.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The study discovered that children's immunization status was greatly influenced by their region. This finding is in line with research from Ethiopia [11,17,27], which found that non-immunization was higher in the Afar, Oromia, and Somali regions. Compared to children in urban areas, children from rural areas were more likely to be in the worst category of immunization status.…”
Section: Discussionsupporting
confidence: 91%
“…This study's findings suggest that not only ANC visiting but also the mother's delivery place can help children's immunization status. This research is in line with previous research in Ethiopia [10,11,31] and Nigeria [32]. Women who attended ANC follow-up were encouraged to protect their children by health professionals, and prenatal care counseling can assist women in remembering to immunize their children.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations